2013
DOI: 10.1007/s00464-013-2908-5
|View full text |Cite
|
Sign up to set email alerts
|

The EURO-NOTES clinical registry for natural orifice transluminal endoscopic surgery: a 2-year activity report

Abstract: Five years since the introduction of NOTES into clinical practice, hybrid techniques have gained considerable clinical application. Several NOTES hybrid cholecystectomy and appendectomy techniques are practicable and safe alternatives to laparoscopic procedures. Also, sigmoidectomies and peroral esophageal myotomies were described, proving feasibility and safety. Nevertheless, the real benefit of NOTES for patients still needs to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Owing to this, natural orifice specimen extraction (NOSE) was introduced as a method of removing bulky specimens without elongating port sites. While NOSE has been frequently applied to colon resections for benign indications [88,89], there have been few reports of transanal and transvaginal NOSE for colorectal cancer [90][91][92]. One study by Park et al (n = 68) compared laparoscopic right hemicolectomy with transvaginal NOSE versus laparoscopically assisted right hemicolectomy for colon cancer, finding decreased postoperative pain and LOS, although, postoperative morbidity was not statistically significantly decreased [93] and wound infection rates with NOSE [94].…”
Section: • • Laparoscopic Techniques and Natural Orifice Specimen Extramentioning
confidence: 94%
“…Owing to this, natural orifice specimen extraction (NOSE) was introduced as a method of removing bulky specimens without elongating port sites. While NOSE has been frequently applied to colon resections for benign indications [88,89], there have been few reports of transanal and transvaginal NOSE for colorectal cancer [90][91][92]. One study by Park et al (n = 68) compared laparoscopic right hemicolectomy with transvaginal NOSE versus laparoscopically assisted right hemicolectomy for colon cancer, finding decreased postoperative pain and LOS, although, postoperative morbidity was not statistically significantly decreased [93] and wound infection rates with NOSE [94].…”
Section: • • Laparoscopic Techniques and Natural Orifice Specimen Extramentioning
confidence: 94%
“…The International Multicenter Trial on NOTES (IMTN) 24 and the German Registry D-NOTES 25 reported good clinical results of TV NOTES. In the IMTN Study, the complication rate was 6.9 %.…”
Section: Transgastric Route In Gastrointestinal Surgery (Dr Hungness)mentioning
confidence: 95%
“…Arezzo et al described 33 NOTES appendectomies, 86 % of which performed with a TG hybrid approach. 24 Gastric closure with a commercially available clip resulted in a 96 % closure rate. The only failure required laparoscopic suturing to close the gastrotomy.…”
Section: Transgastric Route In Gastrointestinal Surgery (Dr Hungness)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the momentum the NOTES technique has gathered, the unavailability of specialized equipments and dedicated platforms have hampered the widespread clinical adoption of NOTES[10]. However, the NOTES procedure is continually evolving with initially-envisioned procedures such as cholecystectomy and appendectomy now giving way to a variety of newer techniques such as peroral endoscopic myotomy (POEM) [11], endoscopic submucosal dissection (ESD) [12], [13], transanal rectal resection [14] and endoscopic full thickness resection [15].…”
Section: Introductionmentioning
confidence: 99%